Sobre a reduç\~ao das matrículas no ensino médio regular - Paulo Roberto Corbucci (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The goal of this discussion text is to identify possible causes of the reduction in regular high school enrollment, which occurred in Brazil since 2005. The text analyzes enrollment data disaggregated according the following variables: i) region; ii) class period; iii) administration level (public/private); iv) school location (rural/urban); v) grades; vi) ages groups; and vii) gender. In addition to enrollment data available from the Ministry of Education`s Basic Education Census, information from the National Household Survey (PNAD), collected by the Brazilian Institute of Geography and Statistics, was also used. The period analyzed was from 2000 to 2006. Some factors were identified as possible explanations for the high school enrollment reduction: i) decreasing number of graduates from elementary education; ii) reduction of age-grade lag in high school level; iii) enrollment increase in youths and adults and adult education (EJA).
Keywords: I21; 330